2016
DOI: 10.18632/oncotarget.10920
|View full text |Cite
|
Sign up to set email alerts
|

L-Ferritin targets breast cancer stem cells and delivers therapeutic and imaging agents

Abstract: A growing body of evidence suggests that cancer stem cells (CSC) have the unique biological properties necessary for tumor maintenance and spreading, and function as a reservoir for the relapse and metastatic evolution of the disease by virtue of their resistance to radio- and chemo-therapies. Thus, the efficacy of a therapeutic approach relies on its ability to effectively target and deplete CSC. In this study, we show that CSC-enriched tumorspheres from breast cancer cell lines display an increased L-Ferriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…Interestingly, we have previously reported that tumorspheres maintain a prevalent CSC phenotype after in vivo injection. 27 As reported in Fig. 4, a lower frequency of H2-K d and a higher frequency and expression of activating ligands, RAE, H60, PVR and Nectin-2, were observed in both the tumorsphere-generated tumors and metastases than in their TUBO-generated analogs.…”
Section: Tumorspheres Derived From the Murine Erbb2supporting
confidence: 61%
“…Interestingly, we have previously reported that tumorspheres maintain a prevalent CSC phenotype after in vivo injection. 27 As reported in Fig. 4, a lower frequency of H2-K d and a higher frequency and expression of activating ligands, RAE, H60, PVR and Nectin-2, were observed in both the tumorsphere-generated tumors and metastases than in their TUBO-generated analogs.…”
Section: Tumorspheres Derived From the Murine Erbb2supporting
confidence: 61%
“…We wonder whether such extra peptide can also be utilized to improve the thermostability of animal ferritin such as HuHF because it has emerged as a popular biotemplate or vehicle in the eld of nanotechnology and nanomedicine. [14][15][16][17][18][19] To this end, we prepared a HuHF mutant termed HuHF-VEP where EP was connected to the N-terminal of HuHF subunit by genetic modication. Aer E. coli cells expressing this mutant were lysed, we puried it to homogeneity as suggested by SDS and native PAGE ( Fig.…”
Section: Enhanced Thermostability Of Huhfmentioning
confidence: 99%
“…[10][11][12] Beneting from the low immunogenicity and the high selectivity for cancer cells which overexpress transferrin receptor 1 (TfR1) for human H-chain ferritin (HuHF), 13 ferritin especially human H-chain ferritin, has attracted attention in materials and medicinal chemistry with use of ferritin nanocages as a vehicle for tumor-imaging agents, anticancer drugs, and bioactive nutrients. [14][15][16][17][18][19] The structure of plant ferritin is different from that of animal ferritin in that plant ferritin only consists of H-type subunits which usually contain an extra peptide (EP) (about 30 amino acid residues) at its N-terminal extremity, while animal ferritin is devoid of such EP domain. 20 This EP domain exhibited the serine-like protease activity and contributed to the storage stability of ferritin.…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulation of Curcumin inside the apoferritin cavity significantly increases its stability and bioavailability while maintaining its therapeutic anti-inflammatory properties [73]. More recently, the theranostic potential of Apo-CUR-Gd was assessed on cancer stem cells (CSCs) [74]. Most evidence suggests that CSCs have the unique biological properties necessary for tumor maintenance and spreading, and function as a reservoir for the relapse and metastatic evolution of the disease by virtue of their resistance to radio-and chemo-therapies [75].…”
Section: Theranostic Use Of Ferritinmentioning
confidence: 99%